2022
DOI: 10.1029/2022gl098741
|View full text |Cite
|
Sign up to set email alerts
|

Closed Fluxtubes and Dispersive Proton Conics at Jupiter's Polar Cap

Abstract: The polar regions of Jupiter's magnetosphere are unlike those of any other planet explored by spacecraft with an internal magnetic field. Mercury (e.g., Anderson et al., 2010), Earth (e.g., Smith & Lockwood, 1996), and Saturn (e.g., Jasinski et al., 2014 all exhibit open magnetic topologies in their polar-most regions, where the solar wind is magnetically connected to each of these planets. Evidence for this solar wind connectivity has been found in magnetic field signatures associated with magnetopause trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Szalay et al. (2022) demonstrated that Jupiter's extreme high latitude polar regions contain magnetospheric heavy ions with energy spectra that are consistent with those in the magnetotail. In parallel, recent results from the Grid Agnostic MHD for Extended Research Applications (GAMERA) global simulations (Zhang et al., 2021) also support a largely closed magnetosphere.…”
Section: Introductionmentioning
confidence: 96%
“…Szalay et al. (2022) demonstrated that Jupiter's extreme high latitude polar regions contain magnetospheric heavy ions with energy spectra that are consistent with those in the magnetotail. In parallel, recent results from the Grid Agnostic MHD for Extended Research Applications (GAMERA) global simulations (Zhang et al., 2021) also support a largely closed magnetosphere.…”
Section: Introductionmentioning
confidence: 96%
“…Unlike heavy ions (O n + /S n + ), which come from the equatorial magnetosphere mainly as pickup‐ions through electron‐impact ionization, proton sources in Jupiter's magnetosphere are less well understood (Bagenal & Dols, 2020). Juno observed up‐welling proton beams contributing 1–5 kg/s of proton outflow from the polar regions of Jupiter (Szalay et al., 2021) along with conic distributions connected to Io's orbit (Clark et al., 2020) and between 3 and 5 R J in the polar‐most regions (Szalay, Clark, et al., 2022). These suggest wave‐particle interactions can also lead to protons being injected into the magnetosphere from Jupiter.…”
Section: Introductionmentioning
confidence: 99%
“…Poleward of the zones is the polar cap—a vast and dynamic region where persistent highly field‐aligned, upgoing energetic electrons have been observed (both inverted V and broadband distributions, albeit spatially separated) simultaneously with upgoing broadband emissions interpreted as the whistler mode (Ebert et al., 2017; Elliott, Gurnett, Kurth, Clark, et al., 2018; Elliott, Gurnett, Kurth, Mauk, et al., 2018; Mauk et al., 2020; Paranicas et al., 2018). There has been ongoing research on plasma processes in this region and this will not be the focus of this study (e.g., Elliott et al., 2020; Masters et al., 2021; Shi et al., 2020; Szalay et al., 2022).…”
Section: Introductionmentioning
confidence: 99%